Preface: 5th International Conference on Management Science and Innovative Education (MSIE 2023) - Zhou, Changcheng; Obadiah, Alberta (Transactions on Economics, Business and Management Research, 2023)
The 5th International Conference on Management Science and Innovative Education (MSIE 2023) was held from November 25-26, 2023 in Singapore. This conference was sponsored by Research Center of Engineering and Science, and was attended by academicians, researchers, entrepreneurs, government agencies and policy-makers, postgraduates from China and all over the world. The aim of MSIE 2023 is to provide a platform for educators, scholars, managers and graduate students from different cultural backgrounds to present and discuss research, developments and innovations in the fields of Social Science. It provides opportunities for the delegates to exchange new ideas and application experiences, to establish business or research relations and to find global partners for future collaboration. MSIE 2023 has received 87 manuscripts. By submitting a paper to MSIE 2023, the authors agree to the review process and understand that papers undergo a peer-review process. Manuscripts will be reviewed by appropriately qualified experts in the field selected by the Conference Committee, who will give detailed comments and-if the submission gets accepted-the authors submit a revised version that takes into account this feedback. All papers are reviewed using a double-blind review process: authors declare their names and affiliations in the manuscript for the reviewers to see, but reviewers do not know each other’s identities, nor do the authors receive information about who has reviewed their manuscript. The Committees of MSIE invest great efforts in reviewing the papers submitted to the conference and organizing the sessions to enable the participants to gain maximum benefit. Hopefully, all participants and other interested readers benefit scientifically from the proceedings and also find it stimulating in the process. We look forward to the exciting moments of the 6th International Conference on Management Science and Innovative Education next year. Changcheng Zhou, Alberta Obadiah Conference Organizing Committee